STIGMATIZATION OF FORCED MARRIAGE IN MONTY TIWA’S ADAPTATION OF GITLICIOUS’S MY LECTURER MY HUSBAND - Masnia Rahayu (Universitas Teknokrat Indonesia, 2022)
The forced marriage and the arranged marriages theme currently become popular in literary works on millennial applications. The facility and privilege of the internet were virtual spaces that were not only a provider of reading materials but also a place for literary production itself such as Wattpad. My Lecturer My Husband, one of the famous Wattpad novels published in 2017, was the work of a Korean boyband fan from Indonesia named Gitlicious (pen name) who idolizes a Korean artist named Lay from the Exo group. In 2020, My Lecturer My Husband was adapted by a well-known producer, Monty Tiwa, into a web series that identified forms of female resistance and the negotiation process of men in forced marriage. Thus, this study aims to analyze forced marriage that reconstructs the negative stigma in Monty Tiwa's adaptation of Gitlicious’s My Lecturer My Husband. This study used the adaptation theory proposed by Linda Hutcheon (2006). To dismantle the ideology of the text, this research used the theory of Butler(1990), which was about the diversity of gender and sexuality expressions. From the results of the analysis, it was found that My Lecturer My Husband reflects the shift in the value of forced marriage contextually and commercially. Ideologically, the text adaptation of Monty Tiwa shows a shift in the stigma of forced marriage attached to the role of parents and a shift in the expression of husband and wife in forced marriage.